Communication—Improvement of Structural Stability during High-Voltage Cycling in High-Nickel Cathode Materials with B2O3 Addition. Issue 5 (10th February 2016) - Han, Seung-Hee; Song, Jun Ho; Yim, Taeeun; Kim, Young-Jun; Yu, Ji-Sang; Yoon, Songhun
Abstract : To improve the structural strength of a high-Ni layered cathode material, boron oxide was added during the calcination process. After boron oxide addition, the external morphology remained invariant, and a slight change of the crystal structure was observed. When the prepared materials were applied as cathodes in lithium-ion batteries, similar capacity and cycle performance with and without boron oxide addition were observed for a 4.3 V cutoff. Increasing the cutoff voltage to 4.5 V induced a more severe structural stress; however, cycle fading was greatly improved with the boron oxide addition. This improvement is associated with a smaller decrease of the compressive strength of the particles and limited formation of cracks within inner particles, which is indicative of more strengthened structure formation with the boron oxide addition in high-Ni cathode materials.